2014
DOI: 10.1002/sec.1061
|View full text |Cite
|
Sign up to set email alerts
|

Introducing touchstroke: keystroke‐based authentication system for smartphones

Abstract: Keystroke dynamics is a well‐investigated behavioural biometric based on the way and rhythm in which someone interacts with a keyboard or keypad when typing characters. This paper explores the potential of this modality but for touchscreen‐equipped smartphones. The main research question posed is whether ‘touchstroking’ can be effective in building the biometric profile of a user, in terms of typing pattern, for future authentication. To reach this goal, we implemented a touchstroke system in the Android platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 30 publications
0
58
0
Order By: Relevance
“…These sensors are capable of providing raw data with high precision and accuracy and are very useful in monitoring the three-dimensional device movements and positioning [18]. In particular, accelerometer readings are used by Grant Ho [19] as it is believed that user have natural orientation while holding the phone during usage.…”
Section: Touch Dynamics For Smart Phonesmentioning
confidence: 99%
“…These sensors are capable of providing raw data with high precision and accuracy and are very useful in monitoring the three-dimensional device movements and positioning [18]. In particular, accelerometer readings are used by Grant Ho [19] as it is believed that user have natural orientation while holding the phone during usage.…”
Section: Touch Dynamics For Smart Phonesmentioning
confidence: 99%
“…Using speed of finger movement: Kambourakis et al [51] introduced a method based on the speed and distance of finger movement on touchscreen devices. This method aims to improve analysis of traditional keystroke dynamics.…”
Section: )mentioning
confidence: 99%
“…They found that despite small performance degradation, software keyboard input still provides feasible features for keystroke dynamics biometric authentication. Kambourakis et al [58] proposed to enhance traditional keystroke dynamics features with additional data on the speed and distance of finger movement on smartphones with touchscreens. This upgrade resulted in an EER of 26% on a 10-digit PIN and an EER of 13.6% on short passphrases.…”
Section: Keystroke Dynamics For Mobile Devicesmentioning
confidence: 99%